First descriptions of diurnal pelagic aggregations of the Argentine red shrimp (Pleoticus muelleri) using a broadband echosounder operating at multiple frequencies - Cabreira, Ariel Gustavo (2023)
This is the first description of diurnal pelagic aggregations of the bottom-dwellingArgentine red shrimp (Pleoticus muelleri) registered with a broadband scientific echosounder. Apelagic trawl net and an underwater video camera were used to validate all the information presentedin this paper. Shrimp aggregations were characterized by increasing frequency response, moreevident at frequencies greater than 120 kHz. Identification of the acoustic signature of this resourceis of particular interest for the development of new methodologies to complement the traditionalswept area method of estimation.